The Impact of Communication Deficiencies on the Recurrence of Audit Findings: Evidence from Inspectorate XYZ - Lyra Raisa Fadhila; Ratna Wardhani (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The recurrence of audit findings suggests that previous audits conducted by Inspectorate XYZ have not effectively led to corrective actions. High-quality audit outcomes are expected to prompt auditees to address identified deficiencies. One contributing factor to these repeated findings is ineffective communication. This study investigates how communication-related issues contribute to the persistence of audit findings within Inspectorate XYZ, drawing on communication theory as its conceptual framework. To explore this issue, the study employs a mixed-methods approach, incorporating surveys, interviews, and document analysis. Thematic analysis is used to interpret the collected data and identify underlying patterns. The findings reveal a critical weakness in the follow-up monitoring process, which significantly contributes to the recurrence of audit findings. The study offers practical implications for both Inspectorate XYZ and the local government, highlighting the need for improved communication strategies and more rigorous follow-up mechanisms. By addressing these gaps, the quality of audits can be enhanced, ultimately supporting more effective governance and accountability within the local government.